Governance approaches in European territorial cooperation programmes and the implications of macro-regional strategies. - Arno van der Zwet; Irene Mcmaster; John Bachtler (European Regional Science Association (ERSA), 2012)
Historically, cooperation across borders was an area of activity dominated by central government actors. However, in the EU some of the earliest institutionalised forms of territorial cooperation are based on bottom-up initiatives involving border municipalities. Current territorial cooperation arrangements continue to be strongly based upon local and regional institutions and actors. Theoretical work on Europeanisation, multi-level governance and new regionalism highlights the increased role of sub-national actors in driving economic development and participating in external networking and cooperation activities. However, the scope and diversity of programmes mean that the opportunities for local and regional partners in terms of influencing the outcomes of programmes are equally varied. There have been significant differences in governance dimensions of programmes. Key questions this paper explores are to what extent bottom-up or top-down approaches are used as well as differences in terms of centralised or localised management or implementation structures. The first part of this paper explores which actors influence key processes in the territorial cooperation cycle at which stage and how these can vary across programmes in order to assess the existence of governance dimensions. The second part of the paper builds on the first section and will specifically focus on the impact that macro-regional strategies have had and can expected to have in the future. These strategies have the potential to significantly affect established territorial cooperation programmes (such as INTERREG). However, its full implications are not fully understood. This section will also explore how these macro-regional strategies may lead to changes in governance approaches and have an impact on the types of partners that European territorial cooperation attracts. The paper's overall aim is to assess to what extent the multi-level governance paradigm extents to the operationalization of territorial cooperation programmes and how future developments will affect it. The paper focuses INTERREG A and B strands of European territorial cooperation but its findings can be applied more broadly. It draws from data collected in relation to a major ESPON study (ESPON TERCO). The paper makes use of data from 8 broad case studies that are based on 224 in depth interviewees as well as 5 in-depth case studies that examined issues of governance, coordination, management and implementation of territorial cooperation. For these 5 in depth case studies a total of 35 respondents were interviewed.
Keywords: 330